Immunosuppressants and risk of Parkinson disease. Issue 7 (31st May 2018) - Racette, Brad A.; Gross, Anat; Vouri, Scott Martin; Camacho‐Soto, Alejandra; Willis, Allison W.; Searles Nielsen, Susan
Abstract: We performed a population‐based case–control study of United States Medicare beneficiaries age 60–90 in 2009 with prescription data (48, 295 incident Parkinson disease cases and 52, 324 controls) to examine the risk of Parkinson disease in relation to use of immunosuppressants. Inosine monophosphate dehydrogenase inhibitors (relative risk = 0.64; 95% confidence interval 0.51–0.79) and corticosteroids (relative risk = 0.80; 95% confidence interval 0.77–0.83) were both associated with a lower risk of Parkinson disease. Inverse associations for both remained after applying a 12‐month exposure lag. Overall, this study provides evidence that use of corticosteroids and inosine monophosphate dehydrogenase inhibitors might lower the risk of Parkinson disease.